The Common Fixed Point of Mappings Satisfying Rational Inequalities in Complete Complex Valued Generalized Metric Spaces - Rakesh Kumar Jaiswal; Dr. Rakesh Kumat Tripath (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper Some common fixed point theorems involving rationalinequalities have been proved and some consequences obtained in Complete Complex Valued Generalized Metric Spaces. Also we have extended this workperiodic point property of common fixed point problem for two rational type contractive mappings .